Is it safe to take Radix Salvia Miltiorrhiza – Radix Pueraria Lobate product with warfarin and aspirin? A pilot study in healthy human subjects. (15th November 2020) - Zhang, Yufeng; Yang, Mengbi; Ho, Nicolas James; Mok, Rosina Yau; Zhang, Zhen; Ge, Beikang; Leung, Ping Chung; Fung, Kwok Pui; Lau, Clara Bik San; Lee, Vincent Hon Leung; Lin, Zhixiu; Wong, Raymond Siu Ming; et al.
Abstract: Ethnopharmacological relevance: Radix Salvia Miltiorrhiza (Danshen) and Radix Pueraria Lobate (Gegen) are officially listed in the Chinese Pharmacopoeia and have long been used together as a Compound Chinese Traditional Medicine (CCTM) for treatment of coronary heart diseases, which are often co–administered with aspirin or warfarin to patients suffering from cardiovascular diseases. Aim of study: Since significant pharmacokinetic and pharmacodynamic interactions between Danshen-Gegen (DG) formula and aspirin/warfarin have been observed in our previous rat studies, the current study was proposed aiming to further verify such pharmacokinetic and pharmacodynamic interactions in healthy human subjects and explore related mechanisms. Materials and methods: A 5–day, multiple dose, five–session clinical trial has been carried out (n = 14) with 2-week washout periods between sessions, during which the subjects would receive different combinations of the medications. Plasma samples were collected for pharmacokinetic evaluation, and whole blood samples were collected for pharmacodynamic evaluation. In addition, an in-vitro mechanistic study is conducted to investigate the role of danshensu on the anti-thrombotic and anti-platelet aggregation effects of warfarin and aspirin respectively. Results: Significant pharmacokinetic and pharmacodynamic herb–drug interactions were observed in healthy human subjects. pharmacokinetically, co–administration of DG with aspirin or warfarin could lead to a moderately increased AUC0→t of aspirin and a decreased AUC0→t of 7–hydroxyl warfarin respectively. The systemic exposure of danshensu (DSS, the marker component of DG) would be significantly increased after co–administration with warfarin. Pharmacodynamically, a reduction in systemic thromboxane B2 concentration was noticed after administration of DG with aspirin, which could be associated with the increased systemic exposure of aspirin and the synergistic effect of danshensu, aspirin and salicylic acid on cyclooxygenase (COX) inhibition. An offset on the warfarin induced soluble thrombomodulin induction was observed after its co-administration with DG, which could be partially attributed to the COX-2 inhibition effect of danshensu. Conclusion: Our results indicated that co–administration of DG with aspirin/warfarin would lead to significant pharmacokinetic and pharmacodynamic herb–drug interactions in healthy human subjects. Graphical abstract: Image 1